Late-Onset Upper Eyelid and Brow Edema as a Long-Term Complication of Hyaluronic Acid Filler Injection. (19th May 2020) - Dubinsky-Pertzov, Biana; Bernardini, Francesco P; Or, Lior; Gazit, Inbal; Hartstein, Morris E
Abstract: Background: Late-onset upper eyelid edema is an uncommonly recognized complication of hyaluronic acid (HA)-based filler injection to the supraorbital area. Objectives: The authors sought to report their experience in diagnosing and managing late-onset upper eyelid edema. Methods: This was a noncomparative, retrospective study of a series of 17 consecutive patients who presented with upper eyelid edema 6 to 24 months after uneventful HA filler injection in the supraorbital area. Results: The study group included 17 female patients. The average time of presentation was 13.9 months. Thirteen patients (76.4%) were satisfied after hyaluronidase and requested no further treatment (observation only); 4 patients (23.5%) elected to receive HA filler re-treatment, with satisfactory results. All patients were followed-up for at least 6 months after the re-treatment. Conclusions: The incidence of late-onset upper eyelid edema is likely to increase as the number of patients undergoing HA filler injection to the supraorbital area increases. Our study emphasizes the importance of recognizing this condition and suggests a suitable noninvasive treatment with satisfying results for both the patient and the physician. Level of Evidence: 4: